A Fast Rechargeable Lithium-Ion Battery at Subfreezing Temperatures. Issue 9 (1st January 2016) - Wang, Chao-Yang; Xu, Terrence; Ge, Shanhai; Zhang, Guangsheng; Yang, Xiao-Guang; Ji, Yan
Abstract : Widespread adoption of plug-in electric vehicles hinges upon fast rechargeability of lithium-ion batteries in all climates. To date, Li-ion batteries subject to quick charging in extreme cold grow lithium dendrites which consume cyclable lithium thus severely shortening battery life and compromise safety. Here we experimentally demonstrate 3C fast charging at −30°C for more than 500 cycles using a new cell structure, the all-climate battery (ACB). Addition of a metal foil creates immense internal heating in the ACB cell upon activation by short pulses of discharge and charge current, allowing charge to 80% state-of-charge in 14 min as opposed to 160 min for a conventional Li-ion cell. Moreover, the ACB cell withstands more than 500 fast-charge cycles while the conventional cell incurs 20% capacity loss after only 12 cycles. The experimental pouch cell of 10 Ah consists of a graphite anode and a NCM622 cathode with a nickel foil coated by polyethylene terephthalate as an internal heating element. We believe that the self-heating ACB cell with 11.4× faster charging and 40× better cycle life enables a ubiquitous, weather-independent fast-charging infrastructure required for affordable vehicle electrification free of range anxiety. This fast rechargeable battery at low temperatures is also essential for outdoor robots and drones as well as can substantially reduce battery size and cost for home and grid energy storage.